2000
DOI: 10.3354/ame021265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of phyto- and bacterioplankton in a high Arctic lake on Franz Joseph Land archipelago

Abstract: Pelagic food web processes with focus on phyto-and bacterioplankton dynamics were followed in a high Arctic lake on Ziegler Island, Franz Joseph Land archipelago, during July and August 1996. The oligotrophlc, permanently ice-covered lake is characterized by a rather short pelagic food web with rotifers representing the highest trophic level. Phytoplankton biomass and net primary production averaging 1.8 pg chl a 1-' and 22 pg C 1-' d-', respectively, decreased dunng the investigation period. Photosynthetic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…A similar conclusion was reached by Reche et al (1996) for another high-mountain lake and by Panzenböck et al (2000) for a high Arctic lake. In most studies, however, the amount of PER was insufficient to meet the BCD (Chrzanowski & Hubbard 1982, Cole et al 1982, Sondergaard et al 1985, Baines & Pace 1991, Descy et al 2002.…”
Section: Per As Bacterial Carbon Supply In Gkssupporting
confidence: 67%
See 2 more Smart Citations
“…A similar conclusion was reached by Reche et al (1996) for another high-mountain lake and by Panzenböck et al (2000) for a high Arctic lake. In most studies, however, the amount of PER was insufficient to meet the BCD (Chrzanowski & Hubbard 1982, Cole et al 1982, Sondergaard et al 1985, Baines & Pace 1991, Descy et al 2002.…”
Section: Per As Bacterial Carbon Supply In Gkssupporting
confidence: 67%
“…The % net PER obtained in GKS is at the upper end of values reported for oligotrophic lakes (e.g. Nalewajko & Schindler 1976, Tilzer & Horne 1979, Cole et al 1982 but similar to values estimated in oligotrophic mountain lakes (Reche et al 1996, Camarero et al 1999) and in Antarctic and Arctic lakes (Parker et al 1977, Panzenböck et al 2000.…”
Section: Variability Of Per In Gksmentioning
confidence: 57%
See 1 more Smart Citation
“…Although several studies focussing on the relationship between phytoplankton and bacterioplankton have shown a close coupling between the release of DOC and BP rates (e.g. Lancelot & Billen 1984, Panzenböck et al 2000, Morán et al 2001, other studies have found that the in situ production of phytoplankton-derived DOC would be insufficient to support the heterotrophic population (e.g. Williams & Yentsch 1976, Bode et al 2001.…”
Section: Uncoupling Between Phytoplankton and Bacteria In The Upper Smentioning
confidence: 99%
“…Thereafter, only minor modifications of practices used in open-water lakes are usually required. Perennial ice-covered lakes have been studied and characterized in this manner in the Antarctic (Bird et al 1991;Priscu et al 1999;Wharton et al 1989) and the Arctic (Barnes 1960;Panzenbock et al 2000). Sampling practices in perennially ice-covered lakes have proceeded as they have in open-water lakes with little attention to instrument-associated "forward" contamination.…”
Section: Introductionmentioning
confidence: 99%